CHARACTERISTICS AND QUALITY Of SOILS UNDER SELECTED FARMING PRACTICES IN SOUTHWESTERN NIGERIA - Eludoyin Adebayo Oluwole; Yetunde Mary Adelere; Olusegun Olufemi Awotoye (Geography, Environment, Sustainability)
This study compared soil properties and quality under five different farm practices in a part of the southwest Nigeria. The study indicated that fewer soil properties accounted for more percentage change in total variance at the fallow and mono-cropping plots than at the forest, crop rotation and alley farming systems. It also showed that soils under fallow and mono-cropping systems exhibited the lowest quality values among the farm practices system studied. The study recommends improved soil management approaches in plots under mono-cropping practices, and extensive soil recovery programmes for fallow lands.